Frequency of antibodies against Neospora caninum y Toxoplasma gondii in dogs with clinical signs of neuromuscular disease - Ruíz R., Nelson (2012)
Toxoplasma gondii and Neospora caninum can cause neuromuscular disorders in dogs. The aim of the Case-Control study was to determine the association between antibodies anti N. caninum and anti-T. gondii in dogs with neuromuscular disorders. Blood samples were collected in 96 and 120 dogs with and without clinical signs of neuromuscular disorders respectively. Serum samples were analyzed by the indirect immunofluorescence test (IFI) for the detection of IgG antibodies, considering positive the sera showing complete fluorescence of the tachyzoite in the dilution 1:50. The frequency for T. gondii was 24.0 ± 8.5% (23/96) and 3.3 ± 3.1 (4/120) for dogs with and without signs of neuromuscular disorders, and for N. caninum was 5.2 ± 4.4 (5/96) and 1.7 ± 2.5 (2/120) for dogs with and without signs of neuromuscular disorders, respectively. There was a significant association between neuromuscular disorders and the presence of anti-T. gondii antibodies but not in the case of the presence of anti-N. caninum antibodies.